2004
DOI: 10.1021/ja0318784
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining To Identify New Plant Triterpenoids

Abstract: Arabidopsis thaliana is a well-established model organism for plant genetics, and its recently sequenced genome reveals a wealth of enzymes similar to known examples that biosynthesize secondary metabolites. We describe experiments that exploit this genomic information to identify novel terpenoids. A predicted open reading frame with high similarity to known oxidosqualene cyclases was shown to convert 3(S)-oxidosqualene to the previously unknown triterpene alcohol (3S,13S,14R)-malabarica-8,17,21-trien-3-ol, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 23 publications
(32 reference statements)
4
91
0
1
Order By: Relevance
“…We describe here the utilization of yeast strains engineered to enhance carbon flux through the mevalonate pathway and accumulate high intracellular levels of farnesyl diphosphate (FPP), a key intermediate in sesquiterpene biosynthesis; the diversion of this intermediate for high-level production of diverse sesquiterpene hydrocarbons in lines engineered with terpene synthase genes; and finally the functional hydroxylation of a sesquiterpene scaffold by coexpression of a cognate cytochrome P450 hydroxylase and cytochrome P450 reductase. Such developments support long range objectives to facilitate functional characterization of putative terpene biosynthetic genes identified in genomic sequencing efforts (Fazio et al, 2004;Shibuya et al, 2006;Wu et al, 2005), to generate large quantities of end-product terpenes sufficient for detailed chemical analyses and diverse biological and industrial testing, as well as to combine tools for molecular evolution of terpene biosynthetic enzymes (Greenhagen, 2003;Greenhagen et al, 2006;Yoshikuni et al, 2006) with a production platform suitable for the molecular dissection of catalytic activities and the discovery of novel terpene compounds.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We describe here the utilization of yeast strains engineered to enhance carbon flux through the mevalonate pathway and accumulate high intracellular levels of farnesyl diphosphate (FPP), a key intermediate in sesquiterpene biosynthesis; the diversion of this intermediate for high-level production of diverse sesquiterpene hydrocarbons in lines engineered with terpene synthase genes; and finally the functional hydroxylation of a sesquiterpene scaffold by coexpression of a cognate cytochrome P450 hydroxylase and cytochrome P450 reductase. Such developments support long range objectives to facilitate functional characterization of putative terpene biosynthetic genes identified in genomic sequencing efforts (Fazio et al, 2004;Shibuya et al, 2006;Wu et al, 2005), to generate large quantities of end-product terpenes sufficient for detailed chemical analyses and diverse biological and industrial testing, as well as to combine tools for molecular evolution of terpene biosynthetic enzymes (Greenhagen, 2003;Greenhagen et al, 2006;Yoshikuni et al, 2006) with a production platform suitable for the molecular dissection of catalytic activities and the discovery of novel terpene compounds.…”
Section: Introductionmentioning
confidence: 96%
“…Overexpression of a gene of interest in either a prokaryotic or eukaryotic expression host has also been exploited. For example, genes for triterpene metabolism have been characterized by their overexpression in yeast, which have an endogenous supply of farnesyl diphosphate (FPP), a necessary precursor, and an internal membrane system necessary for proper expression of these integral membrane bound enzymes and sites for end-product accumulation (Fazio et al, 2004;Shibuya et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other characterized triterpene synthases, such as LUP1 and LUP2 ( Fig. 1), catalyze the formation of nonsteroidal polycyclic triterpenes, among which lupeol and ␤-amyrin are common secondary metabolites (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Genome sequencing projects have revealed that many organisms, most notably Streptomyces, [2,3] but also other bacteria, [33] fungi [34,35] and plants, [36] have the genetic capacity to produce a far greater number of secondary metabolites than have been observed through traditional cultivation methods. Recently, several studies have used these data in genome mining assisted natural product discovery, as exemplified by the isolation of coelichelin, [5] germicidins, [6] halstoctacosanolides [37] and ECO-02 301 [38] from Streptomyces.…”
Section: Discussionmentioning
confidence: 99%